Looking Outside Health Care to Teach Innovation in Physical Therapy Business Practice: Use of Harvard Business School Cases at Emory University. Issue 4 (December 2017) - Kapasi, Zoher F.; Davis, Beth P.
Abstract : Background and Purpose: With profound changes in health care and the need for innovation to deliver exceptional value to patients receiving physical therapy, it is incumbent that students are prepared to look outside health care to adopt business practices from other industries and foster innovation as they begin to practice physical therapy. The purpose of this paper is to describe how the case-based analysis of Harvard Business School (HBS) cases from a variety of industries was implemented to teach business disciplines and promote innovative thinking in Doctor of Physical Therapy students at Emory University. Method/Model Description and Evaluation: The process for developing the course including course content and objectives, pedagogical, methods, student assessment including course evaluation and alumni survey at Emory University is described in this study. In addition, quantitative and qualitative analysis of students' course evaluation outcomes has been described in this paper. Outcomes: A total of 57 students participated in the elective course over the past 4 academic years. Class participation, written assignments, and quantitative analysis of course evaluations indicate that students agree the course objectives were met. Qualitative analysis of anonymous student comments revealed core themes of innovative course format and innovative learning, showing that the course instilled an innovation mindset in our students. Finally, 94% of course alumni survey respondents agreed that the course created an entrepreneurial and innovative mindset that impacted their practice of physical therapy. Discussion and Conclusion: We successfully introduced a course in a physical therapist education program to include training in innovation using HBS cases. To deliver exceptional value to patients receiving physical therapy, we must innovate. Thus, preparation of physical therapist practitioners who can innovate is critical to achieve our vision of optimizing movement to improve human experience and thereby transform society. Abstract : Supplemental Digital Content is Available in the Text.